Circadian Rhythms in Bacterial Sepsis Pathology: What We Know and What We Should Know - Mul Fedele, Malena Lis; Senna, Camila Agustina; Aiello, Ignacio; Golombek, Diego Andres; Paladino, Natalia (Frontiers in Cellular and Infection Microbiology, 2021)
Sepsis is a syndrome caused by a deregulated host response to infection, representing the primary cause of death from infection. In animal models, the mortality rate is strongly dependent on the time of sepsis induction, suggesting a main role of the circadian system. In patients undergoing sepsis, deregulated circadian rhythms have also been reported. Here we review data related to the timing of sepsis induction to further understand the different outcomes observed both in patients and in animal models. The magnitude of immune activation as well as the hypothermic response correlated with the time of the worst prognosis. The different outcomes seem to be dependent on the expression of the clock gene Bmal1 in the liver and in myeloid immune cells. The understanding of the role of the circadian system in sepsis pathology could be an important tool to improve patient therapies.